2002
DOI: 10.1515/cclm.2002.183
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Various Urine Tests in the Jordanian Population with Urinary Tract Infection

Abstract: We compared the performance of leukocyte esterase and nitrite reductase dipstick tests with microscopic examination and uroculture in cases with clinically suspected urinary tract infection (UTI). We studied urine specimens from 504 Jordanian patients which were obtained by the mid-stream clean catch method and analyzed for bacteria. All samples were subjected to culture. Results of urine dipstick tests and pyuria (white blood cells (WBC)/high power field) were compared with urine culture for each sample. Sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The authors suggest that both urine analysis methods can be used for a quick diagnostic. Other authors obtained similar results (Vangone & Russo 1985, Vickers et al 1991, Lohr et al 1993, Al-Daghistani & Abdel-Dayem 2002. Taneja et al (2010) evaluated the usefulness of the reagent strip (leukocyte esterase and nitrite) and of the microscopic examination of the urine for diagnosing UTI and concluded that these techniques must be used jointly for added safety in quickly UTI diagnosing.…”
Section: Discussionmentioning
confidence: 83%
“…The authors suggest that both urine analysis methods can be used for a quick diagnostic. Other authors obtained similar results (Vangone & Russo 1985, Vickers et al 1991, Lohr et al 1993, Al-Daghistani & Abdel-Dayem 2002. Taneja et al (2010) evaluated the usefulness of the reagent strip (leukocyte esterase and nitrite) and of the microscopic examination of the urine for diagnosing UTI and concluded that these techniques must be used jointly for added safety in quickly UTI diagnosing.…”
Section: Discussionmentioning
confidence: 83%
“…The increased risk of infection in diabetic patients can be partially explained by a reduced T-cell mediated immune response and impaired neutrophil function among diabetics (Zhanel, Nicolle, & Harding, 1995). Other factors such as local complications related to neuropathy including impaired bladder emptying and higher glucose concentrations in urine may also play a role in increased incidences of UTI in diabetics (Al-Daghistani & Abdel-Dayem, 2002). Patients with diabetes mellitus react with the health care system more frequently and more intensively than the general population (Hvidberg et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Our results show a lower level of urine SG in patients with only positive urine culture findings than in other two groups even though the mean level of that were within normal range. In addition, false-negative WBC count might be obtained in case of lysis or the absence of inflammatory response in colonized (rather than infected) individuals 11) . Urine culture findings are the reference standard for the diagnosis of UTI, but negative culture findings are often observed in various clinical settings; partially treated bacterial UTIs, viral infections and UTI in the presence of urinary obstruction 1) .…”
Section: Discussionmentioning
confidence: 99%